RELIGIOUS PLURALISM IN BALI PREMODERN AND CONTEMPORARY PERSPECTIVES - Mark Woodward (IAIN Manado, 2019)
AbstractThis paper describes two modes of civic religious pluralism in Bali. The first is adaptive pluralism in which elements of Islam were incorporated into pre-modern Balinese states. Analysis focuses on the way in which Gusti Ayu Made Rai, an eighteenth-century Balinese princess became Raden Ayu Siti Khotijah, one Indonesia’s few widely recognized female Muslim saints. This leads to an alternative reading of Balinese religious history, countering the view that it is a static monolithically Hindu tradition. Rather than turning inward as the surrounding areas embraced Islam, Balinese kingdoms included Muslims and Islam in scared narratives and geographies. Today this integrative strategy functions only at the local level. Pilgrimage to her grave by Indonesian Muslims integrates Hindu Bali into Indonesian society defined in terms of the national ideology Pancasila. The establishment of Pancasila as a hegemonic symbology has led to a new form of parallel pluralism in which all religions are subject to state regulation.Keywords: Bali, Hinduism, Islam, Female Saints, Pluralism, State Symbologies AbstrakMakalah ini menggambarkan dua bentuk keragaman beragama masyarakat di Bali. Yang pertama adalah keragaman adaptif di mana unsur-unsur Islam tergabung dalam kerajaan pra-modern Bali. Analisa berfokus pada saat di mana Gusti Ayu Made Rai, seorang puteri kerajaan Bali abad kedelapan belas menjadi Raden Ayu Siti Khotijah, salah seorang wanita Muslim yang dianggap wali di Indonesia. Hal ini mengarah kepada wacana alternatif tentang sejarah agama orang Bali, yang berlawanan dengan pandangan yang meyakini bahwa Bali merupakan tradisi Hindu yang statis secara monolitis. Alih-alih menutup diri saat wilayah-wilayah di sekitarnya memeluk Islam, kerajaan-kerajaan Bali merangkul kaum Muslim dan ajaran Islam dalam kisah-kisah dan kawasan-kawasan sakral. Saat ini strategi integratif tersebut hanya berfungsi di tingkat lokal. Para peziarah Muslim Indonesia ke makam Sang Puteri menyatukan Bali Hindu ke dalam masyarakat Indonesia mempertegas ideologi nasional Pancasila. Pembentukan Pancasila sebagai sebuah simbologi hegemoni telah mengarah kepada bentuk baru keragaman paralel di mana semua agama tunduk kepada peraturan negara.Kata Kunci: Bali, Hinduisme, Islam, Wali perempuan, Keberagaman, Simbol-simbol Negara.